Correlation between placental weight and birth weight of the newborn and its effect on perinatal outcome: a hospital based cross-sectional study: - Inamdar, Shanti Sampada S.; Kuntoji, Nagarathna G.; Mallapur, Ashalatha; Mural, Prabhu Hanamantappa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The placental weight and its correlation with birth weight have been studied extensively for their potential associations with fetal growth and perinatal outcomes. This study aimed to investigate the correlation between placental weight and birth weight of newborns and evaluate the effects of this correlation on perinatal outcomes. Methods: This hospital-based cross-sectional study included 50 pregnant women with singleton pregnancies without comorbidities. Placental weight was measured immediately after delivery, and birth weight was recorded within the first hour. Perinatal outcomes such as Apgar scores, neonatal intensive care unit (NICU) admission, and respiratory distress were documented. Statistical analysis included descriptive statistics, Pearson’s correlation coefficient, and appropriate tests to analyze the effects of placental weight and birth weight on perinatal outcomes. Results: A positive correlation was observed between placental weight and birth weight of newborns. No significant differences were found in mean birth weight and placental weight across gestational age groups. Lower birth weights and placental weights were associated with adverse perinatal outcomes, including lower Apgar scores, increased NICU admissions, and higher incidence of respiratory distress. Conclusions: The positive correlation between placental weight and birth weight reinforces the crucial role of the placenta in supporting fetal growth and development. Deviations from normal placental weight may signal underlying placental insufficiency or pathological conditions, increasing the risk of adverse perinatal events. Monitoring placental weight and fetal growth during pregnancy may help identify high-risk pregnancies and optimize perinatal outcomes.